A priming dose of protons alters the early cardiac cellular and molecular response to 56Fe irradiation. (February 2016) - Ramadan, Samy S.; Sridharan, Vijayalakshmi; Koturbash, Igor; Miousse, Isabelle R.; Hauer-Jensen, Martin; Nelson, Gregory A.; Boerma, Marjan
Abstract: Purpose: Recent evidence suggests that the heart may be injured by ionizing radiation at lower doses than was previously thought. This raises concerns about the cardiovascular risks from exposure to radiation during space travel. Since space travel is associated with exposure to both protons from solar particle events and heavy ions from galactic cosmic rays, we here examined the effects of a "priming" dose of protons on the cardiac cellular and molecular response to a "challenge" dose of 56 Fe in a mouse model. Methods: Male C57BL/6 mice at 10 weeks of age were exposed to sham-irradiation, 0.1 Gy of protons (150 MeV), 0.5 Gy of 56 Fe (600 MeV/n), or 0.1 Gy of protons 24 hours prior to 0.5 Gy of 56 Fe. Hearts were obtained at 7 days post-irradiation and western-blots were used to determine protein markers of cardiac remodeling, inflammatory infiltration, and cell death. Results: Exposure to 56 Fe caused an increase in expression of α -smooth muscle cell actin, collagen type III, the inflammatory cell markers mast cell tryptase, CD2 and CD68, the endothelial glycoprotein thrombomodulin, and cleaved caspase 3. Of all proteins investigated, protons at a dose of 0.1 Gy induced a small increase only in cleaved caspase 3 levels. On the other hand, exposure to protons 24 hours before 56 Fe prevented all of the responses to 56 Fe. Conclusions: This study shows that a low dose of protons may prime the heart to respond differently to a subsequent challenge dose of heavy ions. Further investigation is required to identify responses at additional time points, consequences for cardiac function, threshold dose levels, and mechanisms by which a proton priming dose may alter the response to heavy ions. Highlights: Iron ions (0.5 Gy) induced proteins related to remodeling in the mouse heart. Iron ions (0.5 Gy) induced markers of cardiac inflammatory infiltration. Given 24 h before iron ions, protons (0.1 Gy) prevented effects of iron ions in the heart. Hence, a low dose of protons may prime the heart to a challenge dose of heavy ions.